Quality of Life of Workers with Disabilities in ‎Jordan and Its Relationship to Some Variables - Al-Abdallat, Bassam (Jordan Journal of Educational Sciences, 2022)
This study aimed to identify the quality of life of workers with disabilities in Jordan and its relationship to some variables. The researcher developed the study tool consisting of (26) items. Validity and reliability of the tool were confirmed. A convenient sample included (154) working individuals with disabilities. Results showed that the level of quality of life for workers with disabilities was average. Significant differences were found for the quality of life due to gender in favor of females. In the age variable, fifferences were in favor of the age group (less than 30 years) and in the variable educational qualification, differences were in favor of the category (secondary or less), while in the variable age of injury, differences were in favor of the age groups (6-15 years) and (more than 16 years). Furthermore, results showed that there were no statistically significant differences attributable to the variables of the of disability and years of experience